2008
DOI: 10.1080/01480540802390775
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin E in Mitigating Methomyl Induced Acute Toxicity in Blood of Male Wistar Rats

Abstract: The present study was designed to evaluate the protective potential of vitamin E, if any, in attenuating the toxic effects induced by acute methomyl treatment in rats. Male Wistar rats, weighing between 230 and 250 g, received either a single oral dose of 9 mg/kg of methomyl, vitamin E alone injected intraperitoneally on alternate days (4 injections) at 50 mg/kg body for 1 week prior to methomyl treatment, or both methomyl plus vitamin E given in a similar manner. The effects of different treatments were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…However, the significant decrease in the hepatic and renal MDA content confirms that the pretreatment with vitamin E and taurine could effectively protect against the hepatic and renal lipid peroxidation induced by MC. These findings are in accordance with the study of Garg et al (2008), who reported that the pretreatment with vitamin E decreased the levels of MDA after single dose of methomyl administration in rat erythrocytes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the significant decrease in the hepatic and renal MDA content confirms that the pretreatment with vitamin E and taurine could effectively protect against the hepatic and renal lipid peroxidation induced by MC. These findings are in accordance with the study of Garg et al (2008), who reported that the pretreatment with vitamin E decreased the levels of MDA after single dose of methomyl administration in rat erythrocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Pretreatment of vitamin E showed decrease in the activities of the SOD and CAT, which indicates that vitamin E and taurine provide protection against MC-induced oxidative stress. Similar results were also observed by Garg et al (2008), who reported that the pretreatment with vitamin E moderated the activity of SOD after single dose of methomyl administration in rat erythrocytes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with these results, Mansour et al found that methomyl decreased the activity of SOD, GST and increased LPO in rat erythrocytes [34]. According to Garg et al acute 24 hr single oral dose of 9 mg/kg of methomyl treatment to rats resulted in a significant increase in the LPO, further GSH levels and the activities of Catalase and GST were found to be significantly decreased following methomyl treatment [68]. Similarly El-Khawaga found that methomyl decreased the activity of SOD, CAT and GST in mice liver [24], and Salama et al (2005) reported that methomyl mode of action could be due to the induction of oxidative stress [69].…”
Section: Histologic Studiesmentioning
confidence: 61%
“…The anemia observed might have been due to the ability of the methomyl to cause acute hemolysis or it might be due to cause oxidative stress, these changes due to an increase rate of breakdown of red cells and/or the toxic effect of methomyl on bone marrow. (14). The reduction in Hb content may be due to increased rate of breakdown of red cells and/or reduction in the rate of formation of RBC's.…”
Section: Discussionmentioning
confidence: 99%